2013
DOI: 10.1556/amicr.60.2013.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic granulomatous disease with markedly elevated IgE levels mimicking hyperimmunoglobulin E syndrome

Abstract: Patients with hyperimmunoglobulin E syndrome (HIES) and chronic granulomatous disease (CGD) have prominently increased immunoglobulin (Ig) E levels. We present a 9-year-old boy with medical history revealing recurrent pneumonia, suppurative lymphadenitis, diarrhea, and otitis. The patient was hospitalized with severe pneumonia. The examination showed tachypnea, crackles at the right and left base of the lung, freckles on his face, red-hair, gingivitis, a high arched palate, and retained primary dentition. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…In this study, we found that most CGD patients have hypergammaglobulinemia. Similar results were also demonstrated by the previous studies . The positive detection rate of pathogens was low in our study, which was similar to that observed in a previous study .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we found that most CGD patients have hypergammaglobulinemia. Similar results were also demonstrated by the previous studies . The positive detection rate of pathogens was low in our study, which was similar to that observed in a previous study .…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were also demonstrated by the previous studies. [18][19][20] The positive detection rate of pathogens was low in our study, which was similar to that observed in a previous study. 8 This might be due to previous long-term antibiotic/antifungal prophylactic therapy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hyper-IgE syndrome (Job syndrome) was excluded in these children because of the clinical course. Elevated IgE occurred in some reported cases of IMD30, none of which were due to loss-of-function mutations (Altare et al, 1998; Caragol et al, 2003; Carvalho et al, 2003; Moraes-Vasconcelos et al, 2005; Luangwedchakarn et al, 2009), and in one case of Chronic Granulomatous Disease, which is a type of MSMD characterized by mycobacterial granuloma formation (Patiroglu et al, 2013). In the later case, IgA deficiency was also reported and no mutations in the STAT3 and DOCK8 genes, characteristic in hiper-IgE syndrome, were found.…”
Section: Discussionmentioning
confidence: 99%
“…An exuberant respiratory inflammation induced by the exposure to inciting antigens and clinically manifested as hypersensitivity pneumonitis (HP) or allergic bronchopulmonary aspergillosis (ABPA) has also been described in CGD [ 2 7 ]. However, HP as an initial presentation of CGD is uncommon and has never been reported.…”
Section: Letter To the Editormentioning
confidence: 99%